EFFORTS TO IMPROVE SALTED FISH QUALITY USING ROTARY DRYING SYSTEM TECHNOLOGY IN GAMPONG KUALA LEUGE, PEUREULAK ACEH TIMUR - Najira Najira; Ica Veronika Maha; Titi Lestia Sriwahyuni; Nurfadillah Nurfadillah; Nurul Kholiza Priani; Hayatul Nurul Fitri; Ririn Mustika Ningrum; Marina Br. Sembiring; Mardudi Mardudi; Maulina Maulina; Indah Piccaso Habinsaran; Danu Abian latif (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2021)
Gampong Kuala Leuge, Peureulak District is one of the National Priority Rural Areas (KPPN) which has been designated as a Capture and Cultivation Minapolitan area by the Ministry of Marine Affairs and Fisheries because most of its people are fishermen. The conditions faced by the community regarding climate and weather, when the weather is hot, it is very easy to dry the fish, while in the rainy season generally, the salted fish will decrease. Thus, household scale competition also faces increasing competition in the digital age because people still use traditional tools and are very dependent on the climate. Therefore, in an effort to balance the competition it is necessary to increase the quality, productivity, and efficiency of the business by taking into account the aspects of food safety through the activities of the Village Development and Empowerment Holistic Program by creating a Rotary Drying System technology as a substitute for stocking to ensure the quality of fish and avoid contamination of microorganisms. From the problems obtained in the form of the dependence of the drying process on weather conditions so that salted fish products are not optimal, conventional marketing techniques have changed to modern ones by providing online shops, and financial management that has not been recorded properly has changed using digital transaction software.